Nailing Jelly to the Wall: Teaching Technology in North American Graduate Archival Education Programs. Issue 1 (14th October 2022) - Poole, Alex H.; Todd‐Diaz, Ashley
ABSTRACT: This exploratory mixed‐methods case study relies on semistructured interviews with tenure‐track faculty members from North American graduate archival programs and a survey of North American graduate students and early career professionals to explore how archival education programs incorporate technology. We asked faculty members not only about the technologies they currently teach, but also their curriculum priorities, topical wish lists, and future challenges to and changes in archival education. We asked students and early career professionals whether they wished their graduate program had better prepared them technologically. Findings revealed that although both groups saw technology and digital curation as current and future areas of priority, students and early career professionals felt ill‐equipped to engage with technology in practice. We discuss the implications of these findings in light of the previous literature and adumbrate opportunities for future research.